Proper orthogonal decomposition for energy convergence of shock waves under severe knock. (1st June 2017) - Xu, Han; Yao, Anren; Yao, Chunde; Gao, Jian
Abstract: Under severe knocks of internal combustion engines, parts like pistons and spark plugs are vulnerable to be damaged by energy convergence of shock waves. Furthermore, the damaged positions and failure modes have a significant regularity. In order to reveal the mechanism and avoid such damage, numerical simulations combined with detonation bomb experiments were conducted to explore the energy convergence phenomenon. Proper orthogonal decomposition was developed to extract the main pressure distributions so that the positions where energy converges can be found and the convergence modes can be recognized. Results show that energy convergence could occur in combustion chambers when severe knocks occurred. The spark plug, central region and edge region of a piston are in typical positions where energy converges. In addition, the position and intensity of such convergence are varied with the chamber shapes. The damaged samples further prove that the engine parts failure is caused by the energy convergence of shock waves. It's shown that the proper orthogonal decomposition is a simple and efficient method to identify the convergence modes and find the convergence positions. This research can provide a theoretical basis for the chamber design to avoid energy convergence as well as the destruction under severe knock. Highlights: Energy convergence of shock waves occurs after severe knock, which is destructive. The positions where energy converges are recognized at spark plug, center and edge. POD applied on pressure fields can identify the positions where energy converges. POD can recognize the convergence modes for various combustion chamber shapes. Combustion chamber shape decides the convergence modes and positions.